Preparation and investigation of photoelectrochemical behaviour of Ce and W Co-Doped Ti02 composite film - Md., R.H.; Chin, W.L.; Wan Jeffrey, B.; Zaira, Z.C.; Hamid, Sharifah Bee Abd (2013)
Ce and W co-doped Ti02photocatalyst composite material has been fabricated by sol-gel method. The composite coated ITO film was then prepared via electrophoretic deposition method.ln order to understand the morphology, structure and optical properties, thecomposite material was characterized with XRD, SEM, UV-vis and FT-IR spectroscopy. The characterization results showed a uniformly distributed porous composite film on ITO substrate. Ce and W as oxides are dispersed on the substrate.A significant photo current was developed under solar simulator irradiation and the value was observed higher as compared with pure titania film electrodes.